Achieving High‐Performance Supercapacitors by Constructing Porous Zinc–Manganese Oxide Microstructures. Issue 8 (16th June 2015) - Gao, Yanping; Zheng, Mingbo; Pang, Huan
Abstract Porous zinc–manganese oxide (ZnMn2O4) microstructures are prepared by calcination using a precursor method, and the material is successfully applied as the supercapacitor electroactive materials in a three‐electrode cell. Due to the unique micro/nanostructure, the as‐prepared sample obtained under the calcination condition of 450 °C for 6 h achieved a high specific capacitance of 1093 F g−1. The electrode also exhibited high cycle stability for 5000 cycles.